Torso dynamics during follow through in baseball batting - Horiuchi, G.; Nakashima, H. (Sports Biomechanics, 2022)
The purpose of this study was to clarify the relationship between the bat swing speed immediately after the ball impact and the dynamics of the torso during the follow through in baseball batting. The batting motion and ground reaction forces acting on each foot for 29 collegiate baseball players were recorded using a motion capture system and two force plates. The biomechanical variables of the torso joint (i.e., the virtual joint that divides the torso between upper and lower) were calculated. For right-handed batters, the torque power of the right rotation in the torso joint was negative. Additionally, the bat head speed immediately after the ball impact was significantly correlated with the negative (i.e., right) peak rotation torque of the torso joint (r = -.635, p < 0.001) and the negative peak power in the right rotation torque of the torso joint (r = -.590, p = 0.001). These results suggest that the left external abdominal oblique muscle is in eccentric contraction during the follow through in baseball batting. Moreover, the results imply that the higher the bat head speed immediately after the ball impact, the higher the possibility to strain the abdominal oblique muscle.